Metode Penilaian Kondisi Jembatan Beton Prategang - Hasanudin, Hasanudin (Jurnal Media Teknik dan Sistem Industri, 2017)
Abstract— Bridges as one of the infrastructure that plays a role in supporting ground transportation, during it service will experience a decrease in conditions caused by the influence of traffic loads, weather effects, environmental influences or other influences. To eliminate the interference required maintenance. A building maintenance including a bridge is preceded by a condition checking activity, and subsequent assessment of conditions. During this examination and assessment of the condition of the bridge refers to the method of inspection and assessment of the conditions set in Bridge Management System (BMS) 1993. There are still weaknesses in the assessment of conditions with Bina Marga BMS caused by the absence of methods of assessing the condition of prestressed concrete bridges. This research is a development of BMS condition assessment, to be used as an assessment of prestressed concrete bridge condition. The object of this research is focused on prestressed precast concrete bridge, namely Kiaracondong Bridge (Bandung) and Cimindi bridge (Cimahi) West Java. The method of assessing the condition undertaken is the examination of damage to the bridge components (physical indicator) through visual inspection, not equipped with destructive and non destructive testing (advanced stage of inspection). Assessment of the conditions developed is the assessment of conditions on the security aspects of the structure and aspects of traffic convenience, where the structure security aspect is the multiplication of the condition of the main part of the building over the bridge. After doing research it can be seen that Cimindi bridge condition value is 3,5-4,25 (need monitoring) and Kiaracondong bridge (very good). The deficiency in the method of assessing the condition in this study is that the assessment of the condition of the bridge is done visually only, so it can not predict the damage to the prestressed concrete components inside. Further examination is required after examination and assessment of this condition is done especially when it is found suspicious things.Keywords: Bridge Management System; Assessment of bridge condition; Prestressed Concrete